Since the problem provides the first term of the geometric sequence, `t_1 = 4` , you need to evaluate the next three terms t_2,t_3,t_4, using the recurrence relation provided, `t_n = -3*t_(n-1)` , such that:

`t_2 = -3*t_1 => t_2 = -3*4 => t_2 = -12`

`t_3 = -3*t_2 => t_3 = -3*(-12) => t_3 = 36`

`t_4 = -3*t_3 => t_4 = -3*36 => t_4 = -108`

**Hence, evaluating the first 4 terms of the geomteric sequence, under the given conditions, yields **`t_1 = 4, t_2 = -12, t_3 = 36, t_4 = -108.`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now